Carbon (1s) NEXAFS spectroscopy of biogeochemically relevant reference organic compounds - Solomon, D.; Lehmann, Johannes; Kinyangi, James; Biqing, L.; Heymann, K.; Dathe, L.; Hanley, K.; Wirick, S.; Jacobsen, C. (Wiley, 2009)
Natural organic matter (NOM) is a highly active component of soils and sediments, and plays an important role in global C cycling. However, NOM has defied molecular-level structural characterization, owing to variations along the decomposition continuum and its existence as highly functionalized polyelectrolytes. We conducted a comprehensive systematic overview of spectral signatures and peak positions of major organic molecules that occur as part of NOM using near-edge x-ray absorption fine structure (NEXAFS) spectroscopy. The spectra of carbohydrates and amino sugars show resonances between 289.10 and 289.59 eV, attributed to 1s-3p/* transitions of O-alkyl (C-OH) moieties. They also exhibited distinct peaks between 288.42 and 288.74 eV, representing C 1s–*C = O transition from COOH functionalities. Amino acids produced a strong signal around 288.70 eV, which can be identified as a C 1s–*C=O transition of carboxyl/carbonyl (COOH/COO-) structures. Spectral features near 285.29 eV were ascribed to C 1s–*C=C transition of ring structure of aromatic amino acids, while spectra between 287.14 and 287.86 eV were attributed to C 1s–*C-H and C 1s–*C-H/3p Rydberg-like excitations from CH and CH2 groups. Phenols and benzoquinone produced strong resonances between 285.08 and 285.37 eV, attributed to the * orbital of C (C 1s–*C=C) atoms connected to either C or H (C–H) in the aromatic ring. The next higher excitation common to both phenols and quinone appeared between 286.05 and 286.35 eV, and could be associated with C 1s–*C=C transitions of aromatic C bonded to O atom in phenols, and to C 1s–*C=O transitions from aromatic C connected to O atom (C-OH) in phenols or to a C=O in p-benzoquinone and some phenols with carbonyl structures, respectively. Nucleobases exhibited complex spectral features with pronounced resonances between 286.02 and 286.84 eV and between 288.01 and 288.70 eV. Molecular markers for black C (benzenecarboxylic acid and biphenyl-4,4'-dicarboxylic acid) exhibit sharp absorption bands between 285.01 and at 285.43 eV, possibly from C 1s–*C=C transition characteristic of C-H sites or unsaturated C (C=C) on aromatic ring structures. These aromatic carboxylic acids also exhibit broad peaks between 288.35 and 288.48 eV, reflecting C 1s–*C=O transition of carboxyl functional groups bonded to unsaturated C. This investigation provides a more comprehensive NEXAFS spectral library of biogeochemically relevant organic C compounds. The spectra of these reference organic compounds reveal distinct spectral features and peak positions at the C K-edge that are characteristic of the molecular orbitals bonding C atoms. Detailed structural information can be derived from these distinctive spectral features that could be used to build robust peak assignment criteria to exploit the chemical sensitivity of NEXAFS spectroscopy for in situ molecular-level spatial investigation and fingerprinting of complex organic C compounds in environmental samples.